2019
DOI: 10.1002/iid3.242
|View full text |Cite
|
Sign up to set email alerts
|

Mouse strain differences in response to oral immunotherapy for peanut allergy

Abstract: Background Promising therapies for food allergy are emerging, mostly based on animal experimentation. However, different mouse strains are used, which may make it hard to compare experiments. The current study investigated whether the immunological differences between C3H/HeOuJ (C3H) and BALB/c mice lead to differences in efficacy of peanut‐specific immunotherapy. Methods After sensitization using peanut extract (PE), C3H and BALB/c mice received oral immunotherapy (OIT… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
11
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
4
1

Relationship

0
9

Authors

Journals

citations
Cited by 15 publications
(13 citation statements)
references
References 32 publications
2
11
0
Order By: Relevance
“…We initially found marked increases in allergen-specific IgA in a trial of OIT for peanut an observation that has subsequently been extended by others to cow's milk and egg OIT (14,(32)(33)(34)(35). Murine models have also documented specific IgA responses following food allergen ingestion and OIT (24,(36)(37)(38). Despite the consistent observation of association between IgA responses and food tolerance in humans and in murine models of food allergy, neither the direct contributions of IgA to tolerance nor the mechanisms thereof have been established.…”
Section: Discussionmentioning
confidence: 86%
“…We initially found marked increases in allergen-specific IgA in a trial of OIT for peanut an observation that has subsequently been extended by others to cow's milk and egg OIT (14,(32)(33)(34)(35). Murine models have also documented specific IgA responses following food allergen ingestion and OIT (24,(36)(37)(38). Despite the consistent observation of association between IgA responses and food tolerance in humans and in murine models of food allergy, neither the direct contributions of IgA to tolerance nor the mechanisms thereof have been established.…”
Section: Discussionmentioning
confidence: 86%
“…In general, mouse models that are currently being used for inducing food allergy have some intrinsic limitations. Presently, mouse models of food allergy are developed with the help of adjuvants (e.g., alum, freund's complete adjuvant and cholera toxin B) in genetically distinct mouse strains (e.g., Balb/c or C3H/HeOuJ) using different routes of sensitization (e.g., intraperitoneal and intragastric) ( 173 175 ). Hence, most studies reporting the efficacy in murine systems tend to fail or show no efficacy when replicated in clinical studies ( 106 ).…”
Section: Current Pitfalls and Future Perspectivesmentioning
confidence: 99%
“…The BLG-p(Man) treatment substantially increased the BLG-specific IgG levels, which outcompeted the increase in IgE, resulting in a reduced IgE/IgG ratio (Figure 5E-G). Interesting, we also observed that the BLGp(Man) treatment significantly induced BLG-specific IgG2a production, an Th1-biased IgG subtype that can be particularly protective against Th2-biased allergic responses in mice 50,52,54,56 . This suggests a specific Th2 suppression mechanism induced by BLG-p(Man) therapy, which was further supported by several in vitro antigen restimulation cytokine analyses (Figure 4D, E; Figure S4G, S7D, E, and S8 F,H).…”
Section: Resultsmentioning
confidence: 64%
“…This can be beneficial in neutralizing allergens, as well as blocking IgE-mediated responses by binding to mast cells and basophils 49 . In C3H mice, IgG2a — a Th1-biased antibody subtype — stands out for its higher increase to various immunotherapies 50, 52, 54, 56 , potentially through the suppression of Th2-driven allergic responses. We further investigate the changes in BLG-specific IgG2a and IgG1 subtypes in response to BLG-p(Man) therapy in allergic mice.…”
Section: Resultsmentioning
confidence: 99%